STRATEGY AND PRICING FOR SUSTAINABLE DEVELOPMENT OF COMPANIES IN THE CONDITIONS OF CIRCULAR ECONOMY - Матросова, Людмила; Кононенко, Яна (SWorldJournal, 2025)
The article considers the relevance of the transition to a circular economy model. The need for rational use of limited resources has been noted. The basic principles of the circular economy have been presented. The importance of ensuring a closed produc